2014
DOI: 10.1111/bjd.12770
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal hydration levels in patients with rosacea improve after minocycline therapy

Abstract: Patients with PPR have increased erythema indices, normal sebum casual levels, a more alkaline centrofacial region and reduced epidermal hydration levels compared with control subjects. Treatment with systemic minocycline reduces erythema and increases hydration, in the absence of any change in skin pH or sebum casual levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Wu et al had also found similar results with increased TEWL and decreased corneous layer water content in rosacea patients 16. But Raghallaigh et al17 found epidermal oil content was slightly higher in papulopustular rosacea patients in comparison to healthy subjects with no significance (P>0.05). In our study, we had decreased epidermal oil content and it is probably because the healthy controls we enrolled had relatively higher oily skin ratios.…”
Section: Discussionmentioning
confidence: 93%
“…Wu et al had also found similar results with increased TEWL and decreased corneous layer water content in rosacea patients 16. But Raghallaigh et al17 found epidermal oil content was slightly higher in papulopustular rosacea patients in comparison to healthy subjects with no significance (P>0.05). In our study, we had decreased epidermal oil content and it is probably because the healthy controls we enrolled had relatively higher oily skin ratios.…”
Section: Discussionmentioning
confidence: 93%
“…Ammonia‐induced alkalization activates stool enzymes lipase and tryptase leading to irritation . In addition, even in acne and rosacea the mean facial SC pH is significantly increased …”
Section: Ph In Inflammatory Skin Diseases and Itchmentioning
confidence: 99%
“…[14][15][16] Reduced stratum corneum hydration and altered skin surface pH were previously noted in patients with rosacea. However, some epidermal changes such as parakeratosis, acanthosis, and exocytosis of inflammatory cells into the epidermis were more common in the PPR cases than in the ETR cases, which may explain the more evident dermal inflammatory reactions in the PPR subtype.…”
Section: Discussionmentioning
confidence: 84%